2016
DOI: 10.3823/2072
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise Program During Breast Cancer Treatment: A Feasibility Study

Abstract: Background: In the last two decades, physical training has been recognized as an important means of prevention and rehabilitation for patients with breast cancer. In Brazil, physical exercise for patients with breast cancer is a new area of study. We aimed to investigate the feasibility of implementing a resistance exercise program for patients undergoing breast cancer treatment and to examine the effects of the resistance exercise program on psychological and physical outcomes. Methods: We conducted a non-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…The authors attribute the improvement to the higher physical competence acquired for the performance of motor tasks. Unlike our data, Arab et al [16] did not nd training effects in the other dimensions [23]. It is possible that this difference is associated with the speci city of the intervention given.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The authors attribute the improvement to the higher physical competence acquired for the performance of motor tasks. Unlike our data, Arab et al [16] did not nd training effects in the other dimensions [23]. It is possible that this difference is associated with the speci city of the intervention given.…”
Section: Discussioncontrasting
confidence: 99%
“…After the intervention, the TG demonstrated a signi cant reduction in the perception of functional limitations of the body, such as movement restrictions and oncologic fatigue. Arab et al [16] in one of the few studies in this scope performed in Brazil, presented similar results, although the protocol applied by them was different, with only resistance training over 12 weeks. The authors attribute the improvement to the higher physical competence acquired for the performance of motor tasks.…”
Section: Discussionmentioning
confidence: 70%
“…strength, 12,13 and BI 15,16 after interventions with physical activity. However, although interventions with combined training (CT), aerobic and resistance training in the same session, are widely used, [17][18][19] the available information is still insipid.…”
Section: Introductionmentioning
confidence: 95%
“…11 Physical training methods, both strength and aerobic, have been used as safe and well tolerated interventions in cancer patients. [12][13][14] Studies have shown a decrease in body fat, and improvements in cardiopulmonary function,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation